Huldiging in Maastricht bij zijn afscheid als kamerlid (?). Vliegen op bordes naast zijn vrouw (?) met bloemen
Huldiging in Maastricht bij zijn afscheid als kamerlid (?). Vliegen op bordes naast zijn vrouw (?) met bloemen.